Cultivating Progress-The Crucial Link between Seed Selection and Agricultural Transformation in India (International Journal of Scientific Research and Management (IJSRM), 2023)
This review article, titled "Cultivating Progress: The Crucial Link Between Seed Selection and Agricultural Transformation in India," intricately examines the pivotal role that seed selection plays in shaping India’s agricultural landscape. Through an exploration of seed diversity, indigenous knowledge, and the Green Revolution, it elucidates how the right choice of seeds has driven innovation, sustainability, and empowerment in Indian farming. The review underscores the importance of climate-resilient seeds, equitable access, and the synergy of biotechnology and genetic diversity conservation. As the agricultural journey continues, this article highlights that seeds are not mere commodities but catalysts for progress, resilience, and abundance